تحليل المحتوى لتيك توك "مركز العربية" في تعليم اللغة العربية: Content Analysis of the “Markaz al-‘Arabiyya” TikTok Platform in Arabic Language Education - Fatimah Syarifani; Nurul Wahdah; Aulia Mustika Ilmiani (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2026)
This study aims to analyze the content and presentation of TikTok @MarkazArabiyah in Arabic language learning. This research uses a qualitative approach with the Critical Discourse Analysis method. The research data consisted of the last ten videos uploaded within a one-month period and were analyzed based on language elements, text, audio, visuals, captions, and the context of their presentation. The last ten videos were purposively selected to represent the current content presentation pattern, while the limitation to one month was done so that the data was in a relatively similar publication context so that the analysis was more consistent. The results of the study show that the content of @MarkazArabiyah presents Arabic language learning through an edutainment approach, which is a combination of educational and entertainment elements. The materials presented include vocabulary, everyday expressions, dialogues, and terms from nahwu and sharaf, packaged through songs, humor, roleplay, animation, and TikTok trends. Discourse-wise, the content is multimodal, contextual, and capable of building the image of Arabic as a modern, communicative, and enjoyable language. Although it has not replaced formal learning, TikTok @MarkazArabiyah serves as a supportive medium that broadens exposure to the Arabic language and increases the digital audience's interest in learning.